Determinants of Corporate Social Responsibility Disclosure and Investor Reaction - Tan, Andreas; Benni, Desmiyawati; Liani, Warda (International Journal of Economics and Financial Issues, 2016)
This paper aims to examine the effect of firm size, media exposure and industry sensitivity to corporate social responsibility disclosure and its impact on investor reaction. The population of the study is the companies listed on Indonesian Stock Exchange. The sample was taken by purposive sampling method, and samples of 53 companies were obtained. Data were analyzed using partial least squares path modeling. The result reveals that firm size, media exposure and industry sensitivity have a significant effect on corporate social responsibility disclosure; firms size, media exposure and industry sensitivity have no direct effect on investor reaction; corporate social responsibility disclosure have direct effect on investor reaction and mediates relationship between firm size, media exposure, industry sensitivity and investor reaction. This present study has two limitations. The first limitation of this study is that using media exposure as a proxy for public pressure may not have been fully fit, but there are still other forms of public pressure such as community lobby and pressure groups that can represent public pressure. The second limitation of this study is that the use of GRI indicators by the companies may not be suitable for the companies since they can not fully apply all of the items. Such difficulties result from the fact that GRI indicators as international guidelines on sustainability reporting are not fully implemented in Indonesia because of cultural and customs differences. The paper is one of the few studies in the academic literature to analyze the effect of three independent variables on the corporate social responsibility disclosure of public companies and investor reaction to the implementation of corporate social responsibility. Keywords: Firm size, Media exposure, Industry sensitivity, Corporate social responsibility disclosure, Investor reaction JEL Classifications: G34, M14, L83